The Influence of Reading Texts on L2 Reading-to-Write Argumentative Writing - Qin, Jingjing; Liu, Yingliang (Frontiers in Psychology, 2021)
Writing from sources is a common requirement in academic writing in the higher education contexts. Much more recent literature on integrated reading-writing tasks has focused on writers’ use of source texts or the validity of integrated writing assessment, while little research has been reported about how the types of reading texts influence the product of integrated reading-writing tasks. This study examines whether the reading texts with similar views or opposing views on a controversial issue have any influence on second language (L2) students’ argumentative writing in terms of the use of argument elements and its overall quality. Fifty-four Chinese second-year university students majoring in English Language Teaching were asked to write an argumentative essay after reading texts with either similar views or opposing views. Results show that students reading texts with opposing viewpoints presented more data, and higher overall quality of argumentative essays than students reading texts with similar viewpoints, although the latter group presented more counterargument data. Pedagogical implications on teaching argumentative writing are discussed.